1999
DOI: 10.1046/j.1460-9568.1999.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of GABAA receptors on cultured hippocampal cells correlate only partially with functional synapses

Abstract: We describe a method to label gamma-aminobutyric acid (GABA)A receptors on the surface of living hippocampal neurons in primary culture, and we compare the distribution of receptors with that of active synapses. To visualize GABAA receptors, the affinity-purified antibody beta3(1-13), recognizing the extracellular N-termini of the GABAA receptor beta2- and beta3-subunits, was used in combination with fluorescent secondary antibodies. The beta2- and beta3-subunits belong to the predominant GABAA receptor subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…Consistent with previous reports (20,25,26,39,53), our immunocytochemical data clearly demonstrate that, in addition to synaptic receptors, also extrasynaptic ones are arranged in clusters and that they become uniformly distributed throughout the cell surface after nocodazole treatment. In agreement with other groups (39, 54 -56), we have found that extrasynaptic receptors in the hippocampus include the ␦ and ␥ 2 subunits.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous reports (20,25,26,39,53), our immunocytochemical data clearly demonstrate that, in addition to synaptic receptors, also extrasynaptic ones are arranged in clusters and that they become uniformly distributed throughout the cell surface after nocodazole treatment. In agreement with other groups (39, 54 -56), we have found that extrasynaptic receptors in the hippocampus include the ␦ and ␥ 2 subunits.…”
Section: Discussionsupporting
confidence: 92%
“…S1I) and 65.3 ± 5.2% were apposed to FM4-64 labeled presynaptic terminals (Fig. S1J, in agreement with previous reports for the proportion of native GABA A R clusters found opposite active FM dye-labeled presynaptic terminals) (16,17). However, only 9.1 ± 1.3% were found apposed to excitatory synapses labeled with homer1 (Fig.…”
supporting
confidence: 91%
“…GABA A receptors can also cluster at glutamatergic terminals in mass hippocampal cultures that contain many more synapses than autapses (Kannenberg et al, 1999;Christie et al, 2002). It is unclear whether presynaptically silent GABA synapses also occur in vivo, although synapses that colocalize postsynaptic receptors for two fast neurotransmitters have been reported in slice preparations (Jonas et al, 1998;Jo and Schlichter, 1999;Walker et al, 2001).…”
Section: Discussionmentioning
confidence: 99%